1999
DOI: 10.1016/s0735-1097(99)00330-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of myocardial injury during radiofrequency catheter ablation by measuring serum cardiac troponin I levels: procedural correlates

Abstract: The degree of myocardial injury incurred by RFA is far more accurately assessed by cTnI levels rather than by CK-MB measurements. Cardiac troponin I levels correlate with the number of RF lesions applied, the site of RFA and the approach to the mitral annulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
63
2
7

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 21 publications
12
63
2
7
Order By: Relevance
“…157 Elevations after ablations are related to the amount of energy used but are usually modest. 161,162 This is also the case for ICD firings and endomyocardial biopsies. There also could be a variety of toxic insults that may exacerbate underlying ischemic heart disease or could function to damage the heart directly.…”
Section: Other Clinical Situations In Which Troponin Levels May Be Elmentioning
confidence: 94%
“…157 Elevations after ablations are related to the amount of energy used but are usually modest. 161,162 This is also the case for ICD firings and endomyocardial biopsies. There also could be a variety of toxic insults that may exacerbate underlying ischemic heart disease or could function to damage the heart directly.…”
Section: Other Clinical Situations In Which Troponin Levels May Be Elmentioning
confidence: 94%
“…A lower cTn level is expected after RF of focal area with few RF lesions. RF ablation of more myocardial tissue in the atria, such as in PV isolation, is expected to have much higher cTn levels [10][11][12][20][21][22][23][24][25]. Previous clinical studies reported contrasting data, in the setting of AF ablation, on cardiac biomarkers levels after cryoballoon ablation compared to RF ablation [7,[13][14][15][16][17][18][19]26].…”
Section: Previous Studiesmentioning
confidence: 99%
“…As several markers have been proven to be useful for diagnosis and evaluation of size of myocardial injury after acute ischemic episode, many authors tried to implement different biomarkers to evaluate and quantify the size of effective ablation lesions [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. On one hand, previous studies have univocally shown humoral biomarkers for myocardial injury to be elevated after radiofrequency (RF) ablation, depending on the amount of energy delivered and the site of ablation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown higher troponin levels after CRYO compared to RF, a finding that suggests CRYO itself causes more myocardial injury and necrosis than RF [17,19]. However, other investigators have found no significant differences between troponin levels after CRYO and RF [7,20]. The contradictory results in previous papers might be explained by the non-randomized design of these studies.…”
Section: Introductionmentioning
confidence: 84%
“…Myocardial injury and cardiac enzyme elevation is common after catheter ablation, a procedure that destroys a small portion of myocardial tissue [9,10,14,20]. Ablation in the ventricles and atrial fibrillation ablations with long linear lesions can result in large necrotic areas and marked cardiac enzyme elevation post procedure [9,11,16,20].…”
Section: Cardiac Injury During Ablationmentioning
confidence: 99%